Large-scale perspective on extreme near-surface winds in the central North Atlantic - Stanković, Aleksa; Messori, Gabriele; Pinto, Joaquim G.; Caballero, Rodrigo (Copernicus Publications, 2024)
This study investigates the role of large-scale atmospheric processes in the development of cyclones causing extreme surface winds over the central North Atlantic basin (30 to 60° N, 10 to 50° W), focusing on the extended winter period (October–March) from 1950 until 2020 in the ERA5 reanalysis product. Extreme surface wind events are identified as footprints of spatio-temporally contiguous 10 m wind exceedances over the local 98th percentile. Cyclones that cause the top 1 % most intense wind footprints are identified. After excluding 16 (14 %) of cyclones that originated as tropical cyclones, further analysis is done on the remaining 99 extratropical cyclones (“top extremes”). These are compared to a set of cyclones yielding wind footprints with exceedances marginally above the 98th percentile (“moderate extremes”). Cyclones leading to top extremes are, from their time of cyclogenesis, characterised by the presence of pre-existing downstream cyclones, a strong polar jet, and positive upper-level potential vorticity anomalies to the north. All these features are absent or much weaker in the case of moderate extremes, implying that they play a key role in the explosive development of top extremes and in the generation of spatially extended wind footprints. There is also an indication of cyclonic Rossby wave breaking preceding the top extremes. Furthermore, analysis of the pressure tendency equation over the cyclones' evolution reveals that, although the leading contributions to surface pressure decrease vary from cyclone to cyclone, top extremes have on average a larger diabatic contribution than moderate extremes.